ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BAWANG HITAM MYRICAN DI BANDUNG - Rajasa Putra, Wahyu; Bayu Dirgantara, I Made (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to determine whether product quality, price perception, promotion, and brand image affect the purchase decision of Myrican black garlic products in Bandung. The fluctuating level of sales of Myrican black garlic is the background of this research problem. Tight competition in the herbal medicine market and a lack of information about the benefits of black onion as an herbal remedy are among the factors that cause uncertain sales. The technique that will be used in this research to determine the data to be studied is non-probability sampling technique, which is a sampling technique that is chosen on the basis of availability or because of the researchers' consideration that they can represent the population. The method used in sampling in this study is purposive sampling. This method uses criteria that have been selected by the researcher in choosing a sample. The research shows product quality, price perception, promotion, and brand image have a significant influence on purchasing decisions. Product quality has the highest significant influence on purchasing decisions. Price perception has the lowest significant influence on purchasing decisions.